Controle postural de idosos em superfícies inclinadas: descritores clássicos e modernos - Barbosa, Renata da Costa (2014)
Understanding how the postural control system is impaired with aging can help identify elderly at risk of falling. In order to study the postural control, center of pressure (CP) behavior can be analyzed. Classical descriptors are commonly used for the CP analysis, however, modern descriptors have been developed aiming to provide more information about the underlying processes involved in the postural control. Aims: Analyze and compare classical and modern descriptors used to analyze the postural control in elderly subjects in quiet standing posture, using data acquired from a force platform in horizontal and inclined surfaces. Methods: The study sample consisted of 17 elderly subjects who remained on a force platform in the upright posture for 70 seconds. The data acquisition was performed with the platform on a horizontal surface and again on a surface inclined at 14 degrees with dorsiflexion and later with plantar flexion of the ankle. For each slope, the procedure was repeated three times with eyes open (EO ) and three times with eyes closed (EC). The initial 10 seconds were discarded and then, CP times series were analyzed in the anteroposterior (AP) and mediolateral (ML) directions. The classical descriptors used were in the time in the frequency domain and the modern descriptors were: Detrended Fluctuations Analysis (DFA), Stabilogram Diffusion Analysis (SDA) and the Sway Density Curve (SDC). Results: In the classical analysis, the results showed significant differences in all comparisons made and, in the modern analysis, the variables provided by the SDA and SDC also showed significant differences between comparisons, however, the DFA did not provide any difference between the conditions. Conclusion: Results provided by the classical variables and by the SDA and the SDC suggest a lower stability of elderly subjects in the inclined surface with dorsiflexion followed by plantar flexion and the eyes closed condition. More studies with the modern descriptors are necessary to better understand their results.